2013
DOI: 10.1177/0886260513496903
|View full text |Cite
|
Sign up to set email alerts
|

Substance Use and Intimate Partner Violence Victimization Among White, African American, and Latina Women

Abstract: The existing literature on intimate partner violence (IPV) does not paint a consistent portrait of the impact of race/ethnicity. In addition, although research has clearly demonstrated that there is a relationship between substance use and IPV, the temporal ordering of these variables is not clearly established. This article seeks to examine the temporal ordering of IPV victimization and drug use using longitudinal data with a nationally representative racially and ethnically diverse sample. Data from Wave III… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 41 publications
1
39
0
1
Order By: Relevance
“…Finally, our data support previous research that found high rates of legal and illegal drug use among college students [ 29 , 60 ]: 80.7 % of our sample population had drunk alcohol and 16.2 % smoked cannabis during the previous twelve months at university. Contrarily to previous research, alcohol or cannabis use were not a predictor of suffering traditional bullying victimization and/or cyber-teasing in this study [ 26 , 61 , 62 ].…”
Section: Discussionmentioning
confidence: 45%
“…Finally, our data support previous research that found high rates of legal and illegal drug use among college students [ 29 , 60 ]: 80.7 % of our sample population had drunk alcohol and 16.2 % smoked cannabis during the previous twelve months at university. Contrarily to previous research, alcohol or cannabis use were not a predictor of suffering traditional bullying victimization and/or cyber-teasing in this study [ 26 , 61 , 62 ].…”
Section: Discussionmentioning
confidence: 45%
“…Eighteen articles were from the USA, 13–30 three from Australia, 31–33 two from New Zealand, 34 35 three from South Africa, 36–38 two from India, 39 40 one from Puerto Rico, 41 one from Spain, 42 one from Korea, 43 one from Nicaragua, 44 one from Kenya, 45 one from Japan, 46 one from the UK 47 and one from Tanzania. 48 Among the 35 cohort studies, 11 were household surveys, 13 19 27 28 32 35 39 43 44 47 49 14 sampled participants from clinical settings, 14 20 21 23 25 26 30 31 33 40 42 45 46 48 7 from schools 16 17 22 24 29 36 50 and 3 from the local community. 15 38 41 Some studies were based on subpopulations of women, including one study (reported in two papers) of women receiving methadone maintenance treatment, 20 21 women attending a clinic with depressive symptoms at baseline, 31 HIV-positive female sex workers 45 and eight studies of pregnant women.…”
Section: Resultsmentioning
confidence: 99%
“…In a study on sexual coercion, risk factors are lower educational level of the mother and of adolescent boys and girls, but especially of adolescent girls (Moraes et al, 2006); unemployment (Taquette et al, 2003) Low educational achievement of women/ girls (ENDESA, 2013) Harmful substance use (Vagi et al, 2013;Lundgren and Amin, 2015;Nowotny & Graves, 2013;Johnson, 2000) Young women who drink heavily, whether infrequently or frequently, have greater odds of experiencing sexual only or sexual and physical IPV compared to abstainers (Waller et al, 2012) Adolescent girls who experience IPV also exhibit other health risk behaviors. According to a representative epidemiologic study (lifetime prevalence of dating violence among U.S. adolescents, controlling for the effects of potentially confounding demographics and risk behaviors): physical and sexual dating violence against adolescent girls is associated with increased risk of substance use, unhealthy weight control behaviors, sexual risk behaviors, pregnancy, and suicidality Drug and alcohol use (Taquette et al, 2003) Substance abuse (men who suffered from alcohol abuse reported more IPV perpetration and victimization in comparison to those who did not consume alcohol; women who suffered from alcohol abuse reported suffering and perpetrating more physical and psychological violence than those who did not) (ENDESA, 2013) Family-related factors: Family conflict, poor parent-child relationships, witnessing violence (Vagi et al, 2013); Witnessing or being a victim of violence (Lundgren and Amin, 2015) Childhood exposure to violence is a consistent predictor of involvement in relationships with IPV for both males and females (referring to dating violence among adolescents and college students in the US) (Gover, Kaukinen & Fox, 2008) Associated factors, both for experiencing and using adolescent IPV included previous experiences of child maltreatment, domestic violence in the family (Barter et al, 2009) Adolescents exposed to marital violence during childhood were more likely to justify the use of violence in dating relationships (Lichter & McCloskey, 2004).…”
Section: Research Monitoring and Evaluationmentioning
confidence: 99%